How light is too light touch: The effect of a short training-based intervention on household poultry production in Burkina Faso - Leight, Jessica; Awonon, Josué; Pedehombga, Abdoulaye; Ganaba, Rasmané; Gelli, Aulo (Elsevier, 2022)
This paper reports on the effects of a training-based intervention seeking to increase household engagement in poultry production in Burkina Faso, analyzing data from a large-scale cluster randomized trial in which 1798 households in 60 communes were observed over a period of three years. The intervention SELEVER — entailing a short series of trainings for households as well as capacity building for local animal health and credit services — had little effect on household poultry production and no effect on profits. There is some evidence of an increase in the utilization of poultry inputs and an associated reduction in poultry mortality, primarily for larger poultry producers; however, there is no evidence of any treatment effects for the smallest producers.